Pharmacist professionals in the prevention of drug abuse: updating roles, and opportunities - Gabriela Arantes Wagner; Arthur Guerra de Andrade (Universidade de São Paulo, 2010)
The objective of this paper was to prepare and provide resources to pharmacists and other healthcare professionals, enabling them to carry out a critical analysis on drug abuse, acquiring knowledge in several areas that effectively contribute to their personal development in this professional field. Professionals play a crucial role in the reduction and prevention of substances abuse, since they are able to advise patient about illicit drugs, psychotropic medicines and alcohol abuse. There is an urgent need to specialize pharmacists to act in the national public health service and contribute to actions aimed at the surrounding community. Esse artigo tem o intuito de preparar e fornecer subsídios a farmacêuticos e outros profissionais de saúde a realizarem uma análise crítica sobre o abuso de drogas adquirindo conhecimento em diversas áreas que contribuam para o seu próprio desenvolvimento nesse campo de atuação. O profissional é fundamental na redução e prevenção ao abuso de substâncias, pois é capaz de aconselhar pacientes sobre o abuso de drogas ilícitas, medicamentos psicotrópicos e álcool. Há urgência na especialização de farmacêuticos para atuarem na saúde pública nacional contribuindo nas ações dirigidas à comunidade.